Recent diagnostic aids in oral squamous cell carcinoma - a detailed review - Gopikrishna Padmanabhan; Madhu Narayan; Rajkumar Krishnan (Oral Oncology Reports)
Oral squamous cell carcinoma (OSCC) is one of the most common malignancies, with a poor prognosis, and must be diagnosed early for better treatment. Because it develops in a multiphase process, it offers the advantage of diagnosing it at an early stage before it manifests as cancer. There are a number of adjuvants available that can aid in the early detection of cancer. With only basic techniques such as conventional examination, exfoliative cytology, and vital staining at first, there has been a huge improvement in the diagnosis. The latest methodologies, molecular techniques, and optical techniques are on the recent front. This article provides an overview of the various supplements available that aid in the diagnosis of precancer and cancer.